Imam an-Nawawi’s “Al-Arba’in” and Its Islamic-Moral Significance - Abdulvahobov Orifjon (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article is dedicated to the famous work “Al-Arba’in” (Forty Hadiths) by the great Muhaddith Imam an-Nawawi. It briefly covers Imam an-Nawawi’s life and scholarly legacy, and analyzes the purpose, content, structure, and educational significance of the book. Through key hadiths included in the collection — such as those on intention (niyyah), faith (iman), excellence (ihsan), halal and haram, brotherhood, sincere advice, and controlling anger — the author highlights the role of “Arba’in” not only as a religious text but also as an important source of moral and social education. The article emphasizes that the work remains highly relevant today for the moral upbringing of youth and spiritual development.